Antecedentes da lealdade do segmento business-to-business (B2B) : um estudo com clientes bancários no Rio Grande do Su - Hentges, Aléxia (Universidade do Vale do Rio dos Sinos, 2011)
Many studies have been made about relationship marketing with the intention of straightening the bonds between companies and clients. But the relationship between two companies (client/supplier) or market B2B is worth of distinction. These consumer companies usually stand out at this relation, in the sense that most of the time their products and services purchases are greater, in amount and price wise. Therefore, these relationships are the objects of this study and have been analyzed in the banking market, trying to explain the influence of the predecessors of loyalty to companies that are bank clients. For that matter, it was proposed a model in which was studied as predecessors of loyalty: satisfaction, affective commitment, perceived value and trust; and some moderational variables as: switching cost, relationship with managers, channel preference, credit, dependency and image, that were evaluated in the direct relation with the loyalty and as moderators of the satisfaction ? loyalty relationship. It was used the multiple linear regression technique to explain the interaction of these predecessors in the relation with the loyalty. The research was based in a survey of the transversal kind, being analyzed a sample of 128 companies from Rio Grande do Sul, that answered a structured poll containing the constructors scales and the questions about the profile of these companies. The main results showed that the variables that were more influential in the companies loyalty with their main business bank were: satisfacion, affective commitment, image and dependency. And in the moderation effects it was possible to observe the intention of the change costs, the relationship with the manager and the client dependency with the satisfaction variable in the relation with the loyalty, being that each one of these effects were tested in an independent way. The negative coefficient in the interaction terms, representing the moderational effects, revealed that clients that have high change cost, high dependency or a good relationship with the manager at their main bank don't need to have a high satisfaction to keep themselves loyal to that bank.
Keywords: B2B; Lealdade; Bancos; Relacionamento; Satisfação; Comprometimento afetivo; Custos de mudança; Regressão linear múltipla; Loyalty; Banks; Relationship; Satisfaction; Affective commitment; Switching cost; Multiple linear regression; ACCNPQ::Ciências Sociais Aplicadas::Administração